A Recourse Goal Programming Approach for the Portfolio Selection Problem - Masmoudi, Meryem; Abdelaziz, Fouad Ben (INFOR. Information systems and operational research, 2012)
This paper presents a recourse goal programming approach to a multiple objective stochastic programming portfolio selection model. The main assumption of our approach is that the investor has a minimum acceptable expected rate of return to achieve under some predefined risk restrictions. The risk restrictions are expressed through constraints on the optimal portfolio beta value. The model and the solution strategy are illustrated with data from securities listed in the S&P100 index.